Applying a Standards-Based Grading Framework Across Lower Level Mathematics Courses. Issue 8 (25th November 2020) - Elsinger, Jason; Lewis, Drew
Abstract : This article describes a framework of Standards-Based Grading suitable for use in a variety of mathematics courses. We detail our experience adapting this framework to various courses, ranging from Pre-calculus to Differential Equations, at four different institutions, including both small liberal arts colleges and large universities, and in class sizes ranging from small to large. Of particular note, we describe our structure of reassessments, including the use of oral reassessments. We also give examples of how this framework provides data allowing instructors to make evidence-based changes to their teaching practice.